2019
DOI: 10.1101/696831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimates of genetic load suggest frequent purging of deleterious alleles in small populations

Abstract: Declining populations are expected to experience negative genetic consequences of 16 inbreeding, which over time can drive them to extinction. Yet, many species have survived in small 17 populations for thousands of generations without apparent fitness effects, possibly due to genetic 18 purging of partially deleterious recessive alleles in inbred populations. We estimate the abundance of 19 deleterious alleles in a range of mammals and find that conversely to current conservation thinking 20 species with hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 58 publications
9
64
1
Order By: Relevance
“…In population genetics, there is tremendous interest in understanding how much of the genome is under selection and the types of mutations underlying much of the phenotypic variation and adaptation in different species. Further, studies have aimed to precisely quantify the amount of deleterious variation segregating in populations to assess the role of population history at influencing deleterious variation and for determining whether small population size could lead to an accumulation of deleterious variants, potentially causing a mutational meltdown and extinction [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In population genetics, there is tremendous interest in understanding how much of the genome is under selection and the types of mutations underlying much of the phenotypic variation and adaptation in different species. Further, studies have aimed to precisely quantify the amount of deleterious variation segregating in populations to assess the role of population history at influencing deleterious variation and for determining whether small population size could lead to an accumulation of deleterious variants, potentially causing a mutational meltdown and extinction [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Marsden et al [4] used GERP to identify deleterious amino acid changing mutations in dogs and wolves and found an increase in deleterious mutations (GERP>4) in dogs and that dogs have a higher summed GERP score across all amino acid changing variants as compared to wolves. Lastly, Valk et al [6] found that, across a range of mammals, species with historically low population size and low genetic diversity have a lower average GERP score of the derived allele than species with large population sizes, suggesting that purging of deleterious alleles reduces genetic load in small populations in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…In population genetics, there is tremendous interest in understanding how much of the genome is under selection and the types of mutations underlying much of the phenotypic variation and adaptation in different species. Further, studies have aimed to precisely quantify the amount of deleterious variation segregating in populations to assess the role of population history at influencing deleterious variation and for determining whether small population size could lead to an accumulation of deleterious variants, potentially causing a mutational meltdown and extinction (Schubert et al 2014;Marsden et al 2016;Henn et al 2016;Valk et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Marsden et al (Marsden et al 2016) used GERP to identify deleterious amino acid changing mutations in dogs and wolves and found an increase in deleterious mutations (GERP>4) in dogs and that dogs have a higher summed GERP score across all amino acid changing variants as compared to wolves. Lastly, Valk et al find that, across a range of mammals, species with historically low population size and low genetic diversity have a lower average GERP score of the derived allele than species with large population sizes (Valk et al, 2019) , suggesting that purging of deleterious alleles reduces genetic load in small populations in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary genomic constraints have been proposed as better predictors for the fitness consequences of mutations [291]. The most used comparative genomic approach is the Genomic Evolutionary Rate Profiling (GERP) score.…”
Section: Evolutionary Genomic Constraints and Genomic Fitnessmentioning
confidence: 99%